Modified metal-organic framework (MOF) compositions, and methods of making and using the same

JP2025026931AActive Publication Date: 2025-02-26NUMAT TECHNOLOGIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024200524
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-07-23
Filing Date
2024-11-18
Publication Date
2025-02-26
Estimated Expiration
2041-03-30

Smart Images

  • Figure 2025026931000001
    Figure 2025026931000001
  • Figure 2025026931000002
    Figure 2025026931000002
  • Figure 2025026931000003
    Figure 2025026931000003
Patent Text Reader

Abstract

To provide modified metal-organic framework (MOF) materials, methods of preparing the same, and processes using the same.SOLUTION: A modified MOF of the invention is modified by impregnating a MOF with an inorganic metal salt. The starting MOF comprises at least one linker or ligand, which comprises an aryl amino group as part of its structure. The modified MOF is able to adsorb either basic or acidic toxic industrial compounds (TICs). The modified MOF can be used to remove TICs from various gaseous streams such as air.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] STATEMENT REGARDING FEDERALLY SPONSORED RESEARCH OR DEVELOPMENT This invention was made with U.S. Government support under Contract No. W911SR18C0031 awarded by the U.S. Army Combat Capabilities Development Command Chemical Biological Center (CCDC CBC) and Contract No. DE-SC0019959 awarded by the Department of Energy. The Government has certain rights in this invention. CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 003,260, filed March 30, 2020, and U.S. Provisional Patent Application No. 63 / 055,737, filed July 23, 2020. Technical Field

[0003] The present invention relates to a METAL ORGANIC FRAMEWORK (MOF) composition having at least one linker molecule with an arylamino group. The MOF is also treated with a metal salt solution after synthesis. The invention further relates to a process for the preparation and activation of the modified MOF composition, as well as a process for using the MOF composition to remove either basic or acidic toxic industrial compounds (TICs) from gas streams. [Background technology]

[0004] Adsorbents are well known and are used in many applications such as air filtration, gas distribution, etc. One particular application of adsorbents is the removal or abatement of contaminants in various gas streams, especially the removal of toxic industrial compounds (TICs) present in air streams. TICs can be classified as either basic or base-forming compounds, or acidic or acid-forming compounds. Typically, adsorbents exhibit adsorption capacity for a range of TICs. However, the adsorption capacity for each TIC depends on the properties of the adsorbent, and there are many materials that are good at adsorbing one TIC but not multiple TICs. For example, the MOF adsorbent Zr(NH2-BDC) has been shown to exhibit good adsorption capacity for NO2 but only a little for ammonia. Filters that require the removal of multiple TICs are routinely required in a wide range of industrial applications. These techniques typically use multiple adsorbents; that is, the capacity for one TIC may be sufficient to remove the target TIC in a particular gas stream but not enough to remove another TIC in the same gas stream. This necessitates the use of multiple adsorbents to remove two or more TICs in a gas stream, such as air. Thus, there is a need for adsorbents that can adequately remove or mitigate two or more TICs. We describe herein a family of adsorbents that can remove multiple TICs from gas streams with high capacity. More specifically, there is a need for MOFs that can remove both basic and acidic TICs.

[0005] Applicant has developed a group of modified MOF materials that have enhanced adsorption capacity for basic compounds such as ammonia while maintaining good adsorption capacity for acidic compounds such as nitrogen dioxide or chlorine. The surprising aspect of the present invention is that when MOFs are modified to enhance their adsorption capacity for basic compounds, their adsorption capacity for acidic gases is not substantially reduced compared to unmodified MOFs. MOF materials capable of adsorbing both acidic and basic gas compounds are prepared by taking a synthetic MOF with good adsorption properties for acidic compounds, impregnating it with a metal salt solution, and then activating it.

[0006] US2019 / 0091503 discloses that MOFs such as UiO-66 can be impregnated with metal compounds such as metal hydroxides or metal hydrides to disperse the metal compounds on the surface or in the pores of the MOF. According to the '503 published application, these impregnated metal compounds are said to have catalytic properties capable of destroying chemical warfare agents (CWAs) such as sarin. The MOFs disclosed in the '503 application differ from the MOFs of the present invention in that the MOFs of the present invention have the ability to adsorb both basic and acidic TICs. Summary of the Invention

[0007] One embodiment of the present invention includes a MOF comprising a corner metal unit, the metal (M) being selected from Zr, V, Al, Fe, Cr, Ti, Hf, Cu, Zn, Ni, Hf, In, Ce, and mixtures thereof, and a linker molecule connecting the metal ion atoms, and a metal (M') inorganic salt impregnated in the MOF, the linker molecule being selected from at least one organic ligand containing an arylamino group, or at least one organic ligand containing an arylamino group and at least one organic ligand not containing an arylamino group. and an organic ligand selected from the group consisting of: and the metal (M') is selected from Li, Na, K, Mg, Ca, Sr, Ba, Mn, Sc, Y, Ti, Zr, Hf, V, Cr, Mo, W, Fe, Co, Ni, Cu, Ag, Zn, Cd, Al, Ga, In, Sn, Pb, and mixtures thereof; and wherein the metal (M') is selected from the group consisting of Li, Na, K, Mg, Ca, Sr, Ba, Mn, Sc, Y, Ti, Zr, Hf, V, Cr, Mo, W, Fe, Co, Ni, Cu, Ag, Zn, Cd, Al, Ga, In, Sn, Pb, and mixtures thereof; and wherein the modified metal-organic framework (MOF) composition has a static ammonia capacity of at least 4 mmol / g measured at 10 Torr and 25° C. and substantially retains its capacity towards acidic TIC.

[0008] A further embodiment is where the M' inorganic salt is selected from a halide, sulfate, carbonate, nitrate, or mixtures thereof. A particular embodiment is where the salt is a halide salt.

[0009] In yet another embodiment, the M' metal is present in an amount from about 0.25 wt.% to about 30 wt.% as the metal.

[0010] Another embodiment of the present invention is where the M metal is selected from Zr, Al, Fe, Cu, or Zn.

[0011] In yet another embodiment, the at least one organic ligand comprising an arylamino group is selected from 2-aminobenzene-1,4 dicarboxylic acid (NH2-BDC), 5-aminoisophthalic acid, 3-aminobenzoic acid, 4-aminobenzoic acid, and mixtures thereof.

[0012] A further embodiment is where the at least one organic ligand that does not include an arylamino group is selected from terephthalic acid (BDC), isophthalic acid, benzoic acid, trimesic acid, acrylic acid, and mixtures thereof.

[0013] Yet another embodiment is where the M' metal is selected from Cu, Zn, Ni, Mn, Mg, or Ca.

[0014] In specific embodiments, the MOF prior to modification as disclosed herein is selected from Zr-UiO-66-NH2, Ce-UiO-66-NH2, Hf-UiO-66-NH2, Fe-MIL-101-NH2, Al-MIL-53-NH2, Cr-MIL-101-NH2, Zn-IROM-3, Cu-BTC-NH2, Ti-MIL-125-NH2, In-MIL-86-NH2, and mixtures thereof.

[0015] Another embodiment is a process for preparing a metal-organic framework (MOF) composition, comprising: a. forming a reaction mixture comprising a metal compound, wherein the metal is selected from Zr, V, Al, Fe, Cr, Ti, Hf, Cu, Zn, Ni, Ce, and mixtures thereof, and a ligand selected from at least one organic ligand comprising an amino group or a combination of at least one organic ligand comprising an amino group and at least one organic ligand not comprising an amino group. b. Reacting the reaction mixture at a certain temperature and time to form the MOF. c. Isolating the MOFs to provide a powder of MOFs. d. Optionally, washing the MOFs with an acid selected from formic acid, hydrochloric acid, nitric acid, sulfuric acid, and mixtures thereof to provide MOFs having free amines. e. optionally forming the MOF powder into a compact; and f. Impregnate the MOF body with an inorganic metal salt (M').

[0016] If a step of forming the MOF powder into a compact is used, the impregnation step can be carried out before, during or after the step of forming the compact. If a step of washing the MOF with an acid is used, the acid wash is preferably carried out before the impregnation step.

[0017] An embodiment of the invention is a process for purifying a gas stream comprising contacting a gas stream containing at least one toxic industrial compound (TIC) with a modified metal-organic framework (MOF) composition under purification conditions, thereby removing at least a portion of at least one TIC from the gas stream, the modified MOF comprising a corner metal unit, the metal (M) comprising a metal ion atom selected from Zr, V, Al, Fe, Cr, Ti, Hf, Cu, Zn, Ni, Hf, In, Ce, and mixtures thereof, and a linker molecule connecting metal ion atoms of the different corner metal units, and an inorganic metal (M') salt impregnated in the MOF, the linker molecule comprising at least one organic ligand comprising an arylamino group, or an arylamino group. and the metal (M') is selected from Li, Na, K, Mg, Ca, Sr, Ba, Mn, Sc, Y, Ti, Zr, Hf, V, Cr, Mo, W, Fe, Co, Ni, Cu, Ag, Zn, Cd, Al, Ga, In, Sn, Pb, and mixtures thereof, and the modified MOF composition has a minimum static ammonia capacity measured at 10 Torr and 25° C. of at least 4 mmol / g, or at least 5 mmol / g, or at least 6 mmol / g, or at least 8 mmol / g, or at least 10 mmol / g, or at least 15 mmol / g, or at least 20 mmol / g. Typically, the static ammonia adsorption capacity is in the range of about 4 to about 25 mmol / g of static ammonia capacity measured at 10 Torr and 25° C.

[0018] A further embodiment is where the gas stream is an air stream and the at least one TIC is selected from ammonia, bromine, boron tribromide, bromine chloride, boron trichloride, bromine trifluoride, bromine pentafluoride, carbonyl fluoride, chlorine, chlorine pentafluoride, chlorine trifluoride, chlorosulfonic acid, dichlorosilane, ethylphosphonic dichloride, fluorine, formaldehyde, hydrogen bromide, hydrogen chloride, hydrogen cyanide, hydrogen fluoride, hydrogen iodide, nitric acid, nitrogen dioxide, nitrogen tetroxide, nitrogen trioxide, phosgene, phosphorus trichloride, silicon tetrafluoride, sulfuric acid, sulfuryl chloride, titanium tetrachloride, tungsten hexafluoride and mixtures thereof.

[0019] In certain embodiments, at least one TIC is a basic TIC, such as ammonia, hi other embodiments, at least one TIC is an acidic TIC, such as nitrogen dioxide or chlorine.

[0020] In another specific embodiment, the modified MOF is formed into a shape selected from pellets, granules, spheres, disks, monoliths, irregular particles, extrudates, and mixtures thereof, with or without the use of a binder in producing these shapes.

[0021] In yet another embodiment, the modified MOF is deposited on a solid support selected from a monolith, a spherical support, a ceramic foam, glass fiber, a woven fabric, a nonwoven fabric, a membrane, a pellet, an extrudate, an irregular particle, and mixtures thereof.

[0022] A specific embodiment is where the solid support is a woven or nonwoven fabric and / or where the solid support or nonwoven fabric is part of a facial mask.

[0023] Another embodiment of the present invention is a device comprising at least one impregnated MOF composition as disclosed herein. In one embodiment, the device further comprises an adsorbent other than the impregnated MOF composition as disclosed herein. In one embodiment, the other adsorbent is a non-impregnated MOF composition. In one embodiment, the other adsorbent is a zeolite. In one embodiment, the other adsorbent is activated carbon. In one embodiment, the device comprises a mixture of at least one impregnated MOF composition as disclosed herein and the other adsorbent. In one embodiment, the device is an assembly comprising a layer comprising at least one impregnated MOF composition as disclosed herein and at least one layer comprising another adsorbent. In one embodiment, the device comprises an assembly of at least two active layers comprising a first layer comprising activated carbon and a second layer comprising a modified MOF composition. In each such device, the modified metal organic framework (MOF) composition comprises a MOF comprising a corner metal unit, the metal (M) comprising a metal ion atom selected from Zr, V, Al, Fe, Cr, Ti, Hf, Cu, Zn, Ni, In, Ce, and mixtures thereof, and a linker molecule connecting the metal ion atoms of the different corner metal units; and an inorganic metal (M') salt impregnated in the MOF, the linker molecule being selected from at least one organic ligand comprising an arylamino group, or a combination of at least one organic ligand comprising an arylamino group and at least one organic ligand not comprising an arylamino group, the metal (M') being selected from Li, Na, K, Mg, Ca, Sr, Ba, Mn, Sc, Y, Ti, Zr, Hf, V, Cr, Mo, W, Fe, Co, Ni, Cu, Ag, Zn, Cd, Al, Ga, In, Sn, Pb, and mixtures thereof; The modified MOF composition is characterized by having a minimum static ammonia capacity of at least 4 mmol / g measured at 10 Torr and 25° C., and by substantially retaining its capacity for acidic TICs compared to the capacity of the MOF composition prior to metal (M') salt impregnation.

[0024] These and other aspects of the invention will become apparent after a detailed description of the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] As used throughout this specification and claims, "substantially" means at least 70%, at least 80%, at least 90% or at least 95%.

[0026] As mentioned above, the present invention relates to a modified metal-organic framework (MOF) composition, a process using the composition, a method for producing the composition, and a device including the composition. The modified MOF of the present invention includes a MOF and a metal (M') salt impregnated in the MOF. Impregnated in the MOF means impregnated on the surface or pores of the MOF.

[0027] MOFs are coordination of metal ions with at least bidentate organic ligands. MOFs are composed of corner metal units that contain metal ion atoms and molecular linkers or ligands that form structures with high surface areas and uniformly sized pores or pores of predefined different sizes. Metals (M) that can be used to prepare MOFs of the present invention include, but are not limited to, Zr, V, Al, Fe, Cr, Ti, Hf, Cu, Zn, Ni, Hf, In, Ce, and combinations thereof. Preferred sets or subsets of the above metals include, but are not limited to, Zr, Al, Fe, Cu, or Zn, and combinations thereof.

[0028] The organic ligands reacting with the metal ions can be selected from at least one organic ligand containing an arylamino group, or a combination of at least one organic ligand containing an arylamino group and at least one organic ligand not containing an amino group. Examples of organic ligands containing an arylamino group include, but are not limited to, 2-aminobenzene-1,4-dicarboxylic acid (NH2-BDC), 5-aminoisophthalic acid, 3-aminobenzoic acid, 4-aminobenzoic acid, and mixtures thereof. Examples of organic ligands not containing an arylamino group include, but are not limited to, terephthalic acid (BDC), isophthalic acid, benzoic acid, trimesic acid, acrylic acid, and mixtures thereof. When the ligands are a combination of at least one organic ligand containing an arylamino group and at least one organic ligand not containing an amino group, the molar ratio of amino-containing:non-amino-containing ligands can vary from 1:99 to 99:1 or 10:90 to 90:10 or 20:80 to 80:20 or 30:70 to 70:30 or 40:60 to 60:40 or 50:50. It is also within the scope of the present invention that amino functionality can be added to the MOF by post-synthesis methods. Amino functionality can be added by post-synthesis addition at the organic ligand or by addition at the corner metal unit. Typically, addition of amino groups at the organic linker involves a covalent bonding reaction, while addition at the corner metal unit will involve the use of chelating species that bind to open metal sites or replace components of the structure that are not the primary structural feature.

[0029] Specifically, arylamino ligands can be added by suspending the MOF in a solvent after synthesis and replacing ligands that do not have arylamino groups with ligands that have arylamino groups. The solvent can be removed and the excess ligands washed with fresh solvent. This washing is repeated until all excess ligands are removed. Examples of organic ligands with arylamino groups include, but are not limited to, 2-aminobenzene-l,4 dicarboxylic acid (NH2-BDC), 5-aminoisophthalic acid, 3-aminobenzoic acid, 4-aminobenzoic acid, and mixtures thereof. Post-synthesis ligand exchange can provide a combination of at least one organic ligand containing an arylamino group and at least one organic ligand not containing an amino group, with the molar ratio of amino-containing:non-amino-containing ligands varying from 1:99 to 99:1, or 10:90 to 90:10, or 20:80 to 80:20, or 30:70 to 70:30, or 40:60 to 60:40, or 50:50.

[0030] Another aspect of the composition of the present invention is the inorganic metal (M') salt impregnated into the MOF. The M' metals that can be used to prepare the composition of the present invention include, but are not limited to, Li, Na, K, Mg, Ca, Sr, Ba, Mn, Sc, Y, Ti, Zr, Hf, V, Cr, Mo, W, Fe, Co, Ni, Cu, Ag, Zn, Cd, Al, Ga, In, Sn, Pb and mixtures thereof. The M' metals are present as metal salts and are impregnated into the surface of the MOF or into the pores of the MOF. It should be noted that the M and M' metals can be the same or different. It is preferred that the M' metal is different from the M metal. The amount of metal salt impregnated into the MOF can vary considerably, but is typically about 1% to about 70% by weight of the metal, or about 5% to about 65% by weight, or about 10% to about 60% by weight, or about 15% to about 55% by weight, or about 20% to about 50% by weight, or about 25% to about 45% by weight. The inorganic M' salt is an anhydrous or hydrated salt selected from halides, sulfates, carbonates, nitrates, or mixtures thereof. In one embodiment, the M' salt is a hydrated or anhydrous halide salt.

[0031] The metal-impregnated MOF of the present invention is characterized by having the following properties. One property is a static ammonia capacity measured at 10 Torr and 25° C. of at least 4 mmol / g, or at least 5 mmol / g, or at least 6 mmol / g, or at least 8 mmol / g, or at least 10 mmol / g, or at least 15 mmol / g, or at least 20 mmol / g. The metal-impregnated MOF is also characterized by substantially retaining its ability to react with acidic TICs compared to non-impregnated MOFs. In particular, it retains about 80% of its adsorption capacity for at least one acidic TIC. One general property of MOFs is a static ammonia capacity of at least 1,000, or at least 1,100, or at least 1,200, or at least 1,300, or at least 1,400 m 2 / g Brunauer-Emmett-Teller (BET) surface area. The metal-impregnated MOFs of the invention are characterized by retaining at least 50% of the BET surface area (SA) of the non-impregnated MOF.

[0032] Another aspect of the present invention is a process for preparing metal-impregnated MOFs. The first step of this synthesis is to prepare the MOF by any synthesis known in the literature. Typically, a solution of the desired metal (M) and ligand is prepared. The metal (M) is introduced as a metal salt. The salt can be a nitrate, halide, sulfate, carbonate, oxyhalide, oxynitrate, oxysulfate, oxycarbonate, etc. Specific examples of salts that can be used include, but are not limited to, zirconium chloride, zirconium bromide, zirconium oxynitrate, zirconium oxychloride, vanadium chloride, copper sulfate, iron chloride, zinc nitrate, or zinc carbonate, and mixtures thereof.

[0033] As mentioned above, the ligands used may be at least one organic ligand containing an arylamino group, or may be a mixture of organic ligands containing at least one arylamino group and organic ligands without arylamino groups. Examples of organic ligands with amino groups include, but are not limited to, 2-aminobenzene-l,4 dicarboxylic acid (NH2-BDC), 5-aminoisophthalic acid, 3-aminobenzoic acid, 4-aminobenzoic acid, and mixtures thereof. Acids and mixtures thereof may be included. Examples of organic ligands without amino groups include, but are not limited to, terephthalic acid (BDC), isophthalic acid, benzoic acid, trimesic acid, acrylic acid, and mixtures thereof. When a mixture of amino and non-amino containing ligands is used in the synthesis, they are added in a molar ratio to achieve the desired molar ratio in the MOF, as described above. The molar ratio of the metal salt to the ligand is also adjusted to achieve a specific molar ratio in the MOF.

[0034] A metal compound, which is a source of metal M, and one or more ligands are mixed in a solvent or mixture of solvents. Examples of solvents that can be used include, but are not limited to, amides, alcohols, water, and mixtures thereof. Specific solvents include dimethylformamide, water, ethanol, isopropanol, and mixtures thereof.

[0035] Optionally, an acid can be present in the reaction mixture during MOF synthesis. In one embodiment, the acid present during MOF synthesis comprises a monocarboxylic acid. In one embodiment, the monocarboxylic acid can be selected from formic acid, acetic acid, benzoic acid, dichloroacetic acid, trifluoroacetic acid, and mixtures thereof. In one embodiment, the acid present during MOF synthesis further comprises an inorganic acid, such as hydrochloric acid, nitric acid, or sulfuric acid, or mixtures thereof. In one embodiment, the acid present during MOF synthesis comprises a mixture of a monocarboxylic acid and an inorganic acid.

[0036] Once the reaction mixture is formed, i.e., all components are solubilized, the reaction mixture is reacted at a temperature and time to form the desired MOF. The reaction temperature can vary from about 50°C to about 200°C, or from about 75°C to about 125°C. The reaction mixture is reacted at the desired temperature for a time selected from about 1 hour to about 78 hours, or from about 8 hours to about 48 hours, or from about 12 hours to about 24 hours. Once the MOF powder is formed, it is isolated by means such as filtration, centrifugation, etc. In some embodiments, the isolated MOF can be washed with an acid composition comprising an inorganic acid. Optionally, the acid wash can be a mixture of one or more inorganic acids and one or more organic acids. Preferred inorganic acids include hydrochloric acid, nitric acid, and sulfuric acid. Preferred organic acids include formic acid. The wet MOF is dried at a temperature of about 40°C to about 250°C, or from about 75°C to about 150°C. The time for drying the wet MOF can vary substantially, but is typically from about 2 hours to about 14 days, or from about 8 hours to about 7 days, or from about 2 days to about 7 days.

[0037] The MOFs are then contacted with a solution of a metal salt that is a source of the metal M', thereby impregnating the MOFs with the metal (M') salt. The M' metal can be selected from any one or more of Li, Na, K, Mg, Ca, Sr, Ba, Mn, Sc, Y, Ti, Zr, Hf, V, Cr, Mo, W, Fe, Co, Ni, Cu, Ag, Zn, Cd, Al, Ga, In, Sn, Pb, and mixtures thereof. The salt can be an inorganic salt selected from one or more of metal nitrates, halides, sulfates, carbonates, and the like, exemplified by halides. The salt can be in the form of a hydrate or anhydrous. Specific examples include, but are not limited to, magnesium chloride, nickel chloride, manganese chloride, zinc chloride, nickel nitrate, magnesium nitrate, nickel sulfate, nickel carbonate. In one embodiment, the metal salt is NiCl26H2O. In one embodiment, the metal salt is MgCl2 (anhydrous). In one embodiment, the metal salt is MnCl24H2O. In one embodiment, the metal salt is ZnCl2 (anhydrous). In one embodiment, the metal salt is a hydrated form of ZnCl2. The metal salt is dissolved in a solvent such as alcohol, water, acetone, and ether. This solution is contacted with the MOFs at a temperature from room temperature to about 65°C for a time from about 1 minute to about 24 hours. The metal-impregnated MOFs are then isolated by filtration, centrifugation, or the like, and dried at a temperature from about 60°C to about 200°C.

[0038] Metal-impregnated MOFs can be formed into a variety of shapes, as described below. When forming the MOF powder into a compact is used, the impregnation step can occur before, during, or after the steps of incorporating the binder and forming the compact.

[0039] In one embodiment, a particular process includes preparing impregnated MOF granules as follows: Mix the dried MOF powder with a binder and thoroughly mix the combination. Binders that can be used include both organic and inorganic binders. Specific examples of inorganic binders include, but are not limited to, clays such as kaolin, attapulgite, boehmite, alumina, silica, metal oxides, and mixtures thereof. Specific examples of organic binders include, but are not limited to, polymers such as polyvinylpyrrolidone (PVP), starch, gelatin, cellulose, cellulose derivatives, sucrose, polyethylene glycol, and mixtures thereof.

[0040] In one embodiment, the MOFs and binder are first thoroughly mixed, and then a solution containing the desired metal (M') salt is mixed into the MOF / binder mixture. The impregnated MOFs are mixed for a time period of about 1 minute to about 24 hours until granules of the desired size are obtained. It is understood that a range of sizes will always be obtained, and therefore the granules will need to be sized, i.e., sieved, to separate granules having the desired size or size range. The size range of the granules will depend on the particular application of the modified MOFs and will depend on various parameters such as pressure drop, packing density, etc. Granules having an average diameter of about 1190 microns (16 mesh) to about 841 microns (20 mesh), or about 841 microns (20 mesh) to about 400 microns (40 mesh), or about 595 microns (30 mesh) to about 297 microns (50 mesh) are desired. By average diameter, it is meant the average diameter assuming an approximately spherical shape. This does not mean that the granules are actually spherical, but rather that the granules will pass through a mesh sieve of a given diameter. Once the desired size granules are obtained, they are dried under vacuum at a temperature of about 50° C. to about 250° C. for a time necessary to reach a pressure of about 0.1 torr, activating the modified MOFs. Other means of incorporating binders into the MOF composition and forming granules or other shaped bodies will be understood by those skilled in the art.

[0041] As described, the metal-impregnated MOF compositions of the present invention are used to remove both basic and acidic contaminants, such as TICs, in gas streams. Gas streams that may need to be purified include, but are not limited to, air streams, industrial gas streams, off-gassing streams, or polluted gas streams. The modified MOFs of the present invention are particularly suitable for removing acidic and basic contaminants from air streams. Contaminants or toxic industrial chemicals that can be removed by the MOFs of the present invention include, but are not limited to, ammonia, bromine, boron tribromide, bromine chloride, boron trichloride, bromine trifluoride, bromine pentafluoride, carbonyl fluoride, chlorine, chlorine pentafluoride, chlorine trifluoride, chlorosulfonic acid, and dichlorosilane. These include, but are not limited to, ethylphosphonic dichloride, fluorine, formaldehyde, hydrogen bromide, hydrogen chloride, hydrogen cyanide, hydrogen fluoride, hydrogen iodide, nitric acid, nitrogen dioxide, nitrogen tetroxide, nitrogen trioxide, phosgene, phosphorus trichloride, silicon tetrafluoride, sulfuric acid, sulfuryl chloride, titanium tetrachloride, tungsten hexafluoride, and mixtures thereof.

[0042] The amount of contaminant (acidic or basic) that the modified MOF can remove is at least 50% or at least 60%, or at least 70%, or at least 80%, or at least 90%, or at least 95%, or at least 99% of the contaminant. In one embodiment, the gas stream is an air stream, the contaminant is NO2, and / or ammonia, and the modified MOF removes at least 80% of the NO2 or at least 80% of the ammonia in the air stream. In another embodiment, a vessel having an inlet and an outlet port is filled with the modified MOF material through which the gas stream is flowed, thereby substantially removing at least one basic contaminant and at least one acidic contaminant. To achieve the desired amount of removal, the gas stream is flowed through the MOF at a rate of about 10 L / min to about 500 L / min, or at a rate of about 30 L / min to about 200 L / min, or at a rate of about 50 L / min to about 120 L / min.

[0043] The modified MOF composition of the present invention can be used in the form of a powder, however, it may be advantageous to form the MOF composition into various shapes, such as pellets, spheres, disks, monoliths, irregular particles, extrudates, etc. Methods for forming these types of shapes are well known in the art. Specific methods for forming granular bodies are described above. The modified MOF material can be formed into various shapes, either by itself or by including a binder. When selecting a binder, it is important to select a binder that does not adversely affect the surface area and adsorption capacity after the desired body is formed. Materials that can be used as binders include, but are not limited to, cellulose, silica, carbon, alumina, and mixtures thereof. Forming the MOF composition into a body can be done before, during, or after impregnation of the MOF.

[0044] The forming process typically involves mixing the modified MOF composition with a solvent or binder + solvent to prepare a thick paste-like material. Once the paste-like material is formed, it can be extruded through a die with holes of about 1-4 mm to form extrudates of various lengths, e.g., 2-50 mm. The paste, or even the powder itself, can be pressed under high pressure to form pellets or tablets. Other means of forming shapes include pressure forming, metal forming, pelletizing, granulation, extrusion, rolling, and marmalizing.

[0045] In yet another aspect of the present invention, the metal-impregnated MOF material can be deposited on articles such as, but not limited to, monoliths, spherical supports, ceramic foams, glass fibers, woven fabrics, nonwoven fabrics, membranes, pellets, extrudates, irregular particles, and mixtures thereof. If the desired article is a monolith, spherical support, ceramic foam, pellets, extrudates, or irregular particles, a slurry of the MOF composition is prepared and deposited on the article by means such as dipping, spray drying, and then dried and optionally calcined. In the case of a membrane, it is possible to form the modified MOF composition directly on the membrane. The metal-impregnated MOF composition of the present invention can be deposited or dispersed on fabrics (woven and nonwoven) or polymers by techniques such as electrospinning, direct crystal growth, and layer-by-layer deposition.

[0046] The metal-impregnated MOF-containing article described in the previous paragraph can be used as is to purify air or other gas streams containing pollutants. The air or other gas stream can be flowed through the article, e.g., monolith, foam, membrane, fabric, whereby the metal-impregnated MOF adsorbs at least a portion of at least one pollutant. The metal-impregnated MOF article can also be placed in various types of rigid containers. For example, the extrudates or tablets or spheres can be contained in a bed through which the air or other gas stream flows. The bed can be placed in various types of housings, such as a filter canister with an inlet and an outlet. The fabric (both woven and non-woven) can also be formed into a filter, such as, but not limited to, a pleated filter. This filter can also be contained in a rigid container, such as a cartridge through which the stream to be treated flows. In certain embodiments, the cartridge is part of a face mask. The pleated filter can also be supported on a frame of various shapes and sizes, through which the gas stream can flow. The frame can be made of various types of materials, such as, but not limited to, metal, wood, plastic, etc. Glass fibers can be formed into glass wool and housed in a rigid filter frame.

[0047] The metal-impregnated MOFs can be used in a device comprising at least one impregnated MOF composition as disclosed herein. In an embodiment, the device further comprises an adsorbent other than the impregnated MOF composition as disclosed herein. In an embodiment, the other adsorbent is a MOF composition that is not metal-impregnated. In an embodiment, the other adsorbent is a zeolite. In an embodiment, the other adsorbent is activated carbon. In an embodiment, the device comprises a mixture of at least one impregnated MOF composition as disclosed herein and another adsorbent. In an embodiment, the device comprises a layer comprising at least one impregnated MOF composition as disclosed herein and at least one layer comprising another adsorbent. In an embodiment, the device comprises an assembly or device comprising a non-layered mixture of layers or particles through which a gas flow, e.g., an air flow, is passed. In a particular embodiment, the first layer in contact with the gas flow is a metal-impregnated MOF layer and the second layer comprises another adsorbent, such as activated carbon, zeolite, or other known adsorbents. In another embodiment, the gas stream may first be contacted with a layer containing another adsorbent and then with a layer containing the modified MOF. Additional layers can be added as needed, such as a hopcalite layer. For example, layers of two different metal-impregnated MOFs can be used, or a layer of metal-impregnated and non-impregnated MOFs can be used. Alternatively, two or more modified MOFs can be mixed to form one layer, or a layer can be composed of metal-impregnated and non-impregnated MOFs. These layers are arranged in beds that can be contained in rigid structures, such as canisters, or in larger containers, such as air streams entering commercial buildings, if large gas streams are to be purified. As mentioned above, the metal-impregnated MOFs in the layers can be in the form of powders or any of the shapes and forms mentioned above.

[0048] Activated carbon, which can be used as another adsorbent as mentioned above, is a highly porous, high surface area adsorptive material with a largely amorphous structure. It is composed of random bridges linking carbon atoms in a predominantly aromatic arrangement. The degree of order varies with the starting material and thermal history. The graphite plates of steam activated coal are somewhat ordered, whereas chemically activated wood has a more amorphous aromatic structure. The random bonding creates a very porous structure with numerous cracks, gaps, and voids between the carbon layers. Activated carbon may be in the form of powder (PAC), granules (GAC), or extrudates (EAC). All three forms are available in a variety of particle sizes.

[0049] Once the modified MOFs and an adsorbent such as activated carbon have been deposited onto a fabric (woven or nonwoven), the fabric can be placed as a layer in a face mask.

[0050] A pleated sheet can be formed containing layers of activated carbon or other sorbent and metal-impregnated MOFs. The pleated sheet can be formed into a variety of configurations, such as a filter canister, or can be housed in a rigid container, such as a frame, which can be made from a variety of materials, including plastic, wood, metal, and cardboard. Working Example Example 1: Synthesis of metal-impregnated Zr(NH2-BDC)

[0051] Zr(BDC-NH2), also known as UiO-66-NH2, was prepared by a literature procedure. In general, the procedure involved dissolving the NH2-BDC ligand in a solvent such as DMF (dimethylformamide), then adding formic acid, then heating the solution to a temperature of about 90°C, adding Zr0(N03), and reacting for a period of time to provide the MOF. The MOF powder was isolated, washed with DMF and acetone, washed with hydrochloric acid, and dried at a temperature of about 100°C for a period of about 12 hours.

[0052] To a 30 mL vial, 200 mg of Zr(NH2-BDC)MOF synthesized above was added. To this powder, 0.936 mmol of either NiCl26H2O, MgCl2(anhydrous), or MnCl24H2O, or ZnCl2(anhydrous) was added, followed by 10 mL of methanol for the NiCl26H2O and MgCl2(anhydrous) samples, or acetone for the ZnCl2(anhydrous) sample. The vial containing the mixture was sonicated for 1 min, after which most of the methanol or acetone was evaporated. The resulting solid was dried at 100 °C overnight. Example 2: Synthesis of MgCl2-modified Zr(NH2-BDC) with binder

[0053] Zr(NH2-BDC) was prepared following the procedure of Example 1, except that the MOFs were dried at 80°C to achieve a hydration level of 10-15%. In a pan mixer, 1948 g of Zr(BDC-NH2) was added along with 3 wt% PVP and the mixture was mixed thoroughly. A mixture of diluted MgCl2 solution was prepared using 328 mL of saturated MgCl2 solution diluted to the approximate pore volume of the MOFs. This was added to the mixture. Mixing of this new mixture was continued until granules were formed. The granules were sieved and the granules of the desired size were dried at 100°C under vacuum until a dynamic pressure (<0.1 Torr) was reached. Example 3: Synthesis of ZnCl2-modified Zr(NH2-BDC) with binder

[0054] Zr(NH2-BDC) was prepared as in Example 1. The material was mixed with colloidal silica solution in a pan mixer to produce a compressible mixture. The material was roll compacted and ground to the desired size. The material was then immersed in a ZnCl2 / acetone solution for approximately 20 hours at a concentration selected to provide the desired zinc loading in the final MOF product. After immersion, the material was air dried and recoated with the same colloidal silica solution. The material was air dried and then dried under vacuum at 100°C until a dynamic pressure (<0.1 Torr) was reached.

[0055] In the following examples, all ammonia sorption and desorption measurements were performed at 25° C. on a Micromeritics 3Flex Surface Characterization Analyzer (Micromeritics, Norcross GA) by dosing to absolute pressure and using a 3 second equilibration interval.

[0056] In the following examples, unless otherwise stated, all N2 gas adsorption and desorption measurements were performed on a Micromeritics Tristar II 3020 system (Micromeritics, Norcross, GA) at 77 K. Between 75-200 mg of sample was employed for each measurement. The specific surface area for N2 was calculated using the Brunauer-Emmet Teller (BET) model in the range of 0.005 < P / Po < 0.05. N2 uptake was measured at P / Po = 0.9, where P / Po is the measurement pressure relative to atmospheric pressure.

[0057] Example 4: Absorption Test Table 1. Zr(NH2-BDC) metal impregnation amount and NH3 absorption amount (mmol / g at 25℃, 10Torr) [Table 1]

[0058] It was found that by using various metal salts to impregnate the Zr(NH2-BDC) MOF, the adsorption capacity of the metal-impregnated MOF for ammonia could be increased. Furthermore, it was shown that increasing the amount of metal salt impregnated into the MOF increases the amount of ammonia adsorption. However, as expected, the surface area decreases with increasing metal salt loading.

[0059] The Cl2 absorption was measured as follows: Cl2 gas was injected into the mixed ballast and then 10,000 mg / m 3 The ballast contents were then mixed with a dilution air stream under dry conditions to produce a challenge concentration of 2,000 mg / m 3The mixed gas flow was passed through an adsorbent bed immersed in a temperature-controlled water bath at 20°C. Approximately 50 mm 3 was packed into a tube with an internal diameter of 4 mm, corresponding to a bed depth of 4 mm and a residence time of approximately 0.15 s. The effluent stream was then passed through a continuously operated Hewlett-Packard 5890 Series II gas chromatograph equipped with a photoionization detector with an 11.7 eV lamp. The loading was calculated by integrating the breakthrough curve at saturation. Table 2. Zr(NH2-BDC) metal impregnation and Cl2 absorption at 25°C and 10 torr [Table 2]

[0060] Table 2 shows that Zr(NH2-BDC) impregnated with nickel chloride or magnesium chloride retains the chloride (acidic TIC) adsorption capacity of the unimpregnated MOF. This is unexpected, given the increased ammonia adsorption of the same metal-impregnated MOFs (see Table 1). The ability of MOFs to adsorb significant amounts of both basic and acidic TICs has not been observed before. Example 5: Breakthrough test

[0061] A fixed amount of Zr(NH2-BDC) (0.25 g) was loaded into the breakthrough system. The first sample was unimpregnated with metals, while the others were impregnated with metals as listed in Table 3. After nitrogen purging, a stream of 250 ppm ammonia in He gas was introduced and passed through the MOF at 50 standard cubic centimeters per second (sccms) at 25 °C. The breakthrough time was recorded when the outlet concentration was measured at 100 ppm. Table 3. Effect of metal impregnation on NH3 breakthrough of Zr(NH2-BDC) [Table 3]

[0062] The results in Table 3 show that impregnating the Zr(NH2-BDC) MOF with metal salt (MgCl2) increases the breakthrough time by up to 93%. The breakthrough depends on the concentration of the metal salt, with the maximum breakthrough occurring at a magnesium loading of 8 wt%.

[0063] Although the foregoing refers to particular embodiments, it will be understood that the invention is not so limited. Those skilled in the art will recognize that various modifications can be made to the disclosed embodiments and such modifications are intended to be within the scope of the invention.

Claims

1. a MOF comprising corner metal units, the metal (M) comprising a metal ion atom selected from Zr, Al, Fe, Cu, Zn, and mixtures thereof, and a linker molecule connecting the metal ion corner atoms; and an inorganic metal (M') salt impregnated in the MOF; the linker molecule is selected from at least one organic ligand comprising an arylamino group, or a combination of at least one organic ligand comprising an arylamino group and at least one organic ligand not comprising an arylamino group; The organic ligand containing an arylamino group is 2-aminobenzene-l,4-dicarboxylic acid (NH 2 -BDC), 5-aminoisophthalic acid, 3-aminobenzoic acid, 4-aminobenzoic acid and mixtures thereof; The organic ligand not containing an arylamino group is selected from terephthalic acid (BDC), isophthalic acid, benzoic acid, trimesic acid, acrylic acid, and mixtures thereof; The metal (M') is selected from Cu, Zn, Ni, Mn, Mg, Ca, and mixtures thereof; has a static ammonia capacity of at least 4 mmol / g measured at 25° C. and 10 Torr and substantially retains its capacity for acidic TIC; The metal (M') salt is selected from anhydrous or hydrated halides, sulfates, carbonates, nitrates, or mixtures thereof; Metal-impregnated metal-organic framework (MOF) compositions.

2. 2. The metal-impregnated metal-organic framework (MOF) composition of claim 1, wherein the metal (M') is present in an amount of 1% to 70% by weight as the metal.

3. 3. The metal-impregnated metal-organic framework (MOF) composition according to claim 1 or 2, characterized in that it comprises a binder selected from an organic binder, an inorganic binder or a mixture thereof.

4. 4. The metal-impregnated metal-organic framework (MOF) composition of claim 1, wherein the MOF composition is formed into a shape selected from pellets, granules, spheres, disks, monoliths, irregular particles, extrudates, and mixtures thereof.

5. 5. A method for purifying a gas stream comprising contacting the gas stream containing at least one toxic industrial compound (TIC) with a metal-impregnated metal-organic framework (MOF) composition according to any one of claims 1 to 4 under purification conditions, thereby removing at least a portion of the at least one toxic industrial compound from the gas stream.

6. 5. An apparatus for purifying a gas stream comprising the metal-impregnated metal-organic framework (MOF) composition of claim 1, comprising: The device is characterized in that the metal-impregnated metal-organic framework (MOF) composition is deposited on a solid support selected from a monolith, a spherical support, a ceramic foam, a glass fiber, a woven fabric, a nonwoven fabric, a membrane, a pellet, an extrudate, an irregular particle, and mixtures thereof.

7. 7. The device of claim 6, wherein the solid support is a woven or non-woven fabric.

Citation Information

Patent Citations

  • In-situ preparation method and application of Ag / AgCl / NH2-MIL-101(Fe) composite photocatalyst with spindle appearance

    CN105498844A

  • Multi-component adsorption material

    JP1990180633A

  • Metal complex and method for producing the same

    JP2011037794A

  • Methods for Electrochemically Induced Cathodic Deposition of Crystalline Metal-Organic Frameworks

    US20120297982A1

  • Decontaminating agent for chemical warfare agent (CWA), method of decontaminating CWA using the same and product including the same

    US20190091503A1